2018 International Conference on Manipulation, Automation and Robotics at Small Scales (MARSS) 2018
DOI: 10.1109/marss.2018.8481156
|View full text |Cite
|
Sign up to set email alerts
|

Some Examples of Path Following in Microrobotics

Abstract: After reviewing the various motion generation strategies (waypoint sequence, trajectory tracking and path following), this paper suggests that path following is probably the best strategy at small scales. This is illustrated by three examples coming from biomedical applications: endoscopic laser steering, magnetic manipulation of microswimmers and navigation of a surgical tool under anatomical constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The only required measurements for implementing our proposed control laws are the COM Cartesian coordinates given by p x and p z . The angle θ in (17) and the magnitude |p| are the polar coordinates of the position vector p = [p x , p z ] .…”
Section: Dynamical Model Of Magnetic Helical Microswimmersmentioning
confidence: 99%
See 1 more Smart Citation
“…The only required measurements for implementing our proposed control laws are the COM Cartesian coordinates given by p x and p z . The angle θ in (17) and the magnitude |p| are the polar coordinates of the position vector p = [p x , p z ] .…”
Section: Dynamical Model Of Magnetic Helical Microswimmersmentioning
confidence: 99%
“…The typical control approach in microrobot motion control literature relies on asymptotic tracking of suitably designed reference signals either in the form of a sequence of waypoints or in the form of time-based trajectories. Dahroug et al [17] have recently shown via experiments that trajectory tracking control strategies are not robust to time delays and may create geometric deviations from the desired paths in low Reynolds swimming. Indeed, as demonstrated by Aguiar et al [18], trajectory tracking controllers for even LTI systems are subject to performance limitations in the presence of structural system constraints such as nonminimum phase zeros.…”
Section: Introductionmentioning
confidence: 99%
“…However, trajectory tracking methods are less appropriate for medical applications as discussed in ref. [23], since the trajectory controller is limited in terms of accuracy and stability (e.g., when dealing with complex geometric curves with high curvatures) and more complicated to implement compared to a path-following scheme. Thereby, the previous work 6 assembled individual tasks (i.e., both the RCM and the path-following tasks) to perform a complex motion within the patient body by handling a straight tool.…”
Section: (B))mentioning
confidence: 99%
“…Consequently, instead of using a 3D trajectory tracking technique, we opted for a 3D pathfollowing scheme more adequate to the clinical requirements. 23 Recently, in ref. [26], we demonstrated the preliminary benefits of this approach in the case of middle ear surgery (using a laboratory Projected 2D point onto the path S p to be followed; t Small time step; e rcm Angular error of the alignment task; e rcm Time derivative of the angular RCM error;…”
Section: Medical Gesture As a 3d Path-following Schemementioning
confidence: 99%
“…Looking at the path following problem, it can be divided into two parts: detection and path following [3], [4]. As regards the path detection, Hough transform [5] and its further developments [6], [7] are considered the most valuable solutions in the literature to cope with the task.…”
Section: Introductionmentioning
confidence: 99%